Phytotoxic substances present in annoni-2 grass - Coelho, Rogério Waltrick (2014)
A greenhouse investigation was conducted throughout 1982 to detect the presence of phytotoxic substances in the annoni-2 grass (Eragrostis plana Nees) plants. Ryegrass (Loilum multiflorum Lam.), white clover (Trifolium repents L.) and birdsfoot trefoil (Lotus comiculatus L.) plants were selected as testers. Three experiments were conducted. The results showed that the seed germination of white clover was inhibited significantly; the same occurred with the development of the aerial part of the seedlings. The ryegrass seedlings development was very poor in both aerial part and in the roots. Birdsfoot trefoil seed germination and seedlings growth were normal. Irrigation of ryegrass plants with water extracts of different plant parts of annoni-2 grass resulted in a stimulatory growth effect. It was concluded that the plants of this grass released phytotoxic substances to the environment which remained biologically active in the soil. These phytotoxic substances released were specific to the inhibited species. In the plants of this grass there is an interspecific allelopathy.